(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Synthesis of carbon nanotubes in flames has become highly attractive due to its rapid, inexpensive, and simple method of production. The study of flame synthesis of carbon nanotubes revolves around the control of flame and catalyst parameters to increase the synthesis efficiency and to produce high quality nanotubes. The control parameters include flame temperature, concentration of carbon source species, catalyst type, equivalence ratio, and fuel type. Carbon nanotubes which are produced with rapid growth rate and possess high degree of purity and alignment are often desired. The present study reviews various optimization techniques from the advanced studies of chemical vapour deposition which are applicable for the synthesis of nanotubes in flames. The water-assisted and catalyst free synthesis are seen as possible candidates to improve the growth rate, alignment, and purity of the synthesized nanotubes. The state-of-the-art of the flame synthesis modelling at particle and flame scales are reviewed. Based on the thorough review of the recent experimental findings related to the catalytic growth of nanotube, possible refinement of the existing particle scale model is discussed. The possibility of two-way coupling between the two scales in computational fluid dynamics may be a major contribution towards the optimization of the flame synthesis.